Five puptacular tales! a collection of five Step 1 and Step 2 early readers - Depken, Kristen L; Petrossi, Fabrizio; Smith, Geof; Tillworth, Mary; MJ Illustrations (Group) (New York Random House, 2016)
The puppies of the PAW Patrol have a series of rescues and adventures
Chase's space case / by Kristen L. Depken ; illustrated by MJ Illustrations -- Rubble to the rescue! / by Kristen L. Depken ; illustrated by MJ Illustrations -- Chase is on the case! / by Geof Smith ; illustrated by Fabrizio Petrossi -- Pit crew pups / by Kristen L. Depken ; illustrated by MJ Illustrations -- King for a day! / by Mary Tillworth ; illustrated by MJ Illustrations
At head of title: Nickelodeon PAW Patrol
1 2
Keywords: Dogs -- Juvenile fiction; Dogs; Rescue work -- Juvenile fiction; Rescue work; Short stories; Short stories; Dogs -- Fiction; Rescue work -- Fiction; Short stories; Fiction; Juvenile works